2011
DOI: 10.1007/s00415-011-6006-0
|View full text |Cite|
|
Sign up to set email alerts
|

Serum levels of cytokines and C-reactive protein in acute ischemic stroke patients, and their relationship to stroke lateralization, type, and infarct volume

Abstract: There is increasing evidence that inflammation plays an important role in the progression of acute ischemic stroke (AIS). The primary aims of this study were to examine the serum levels of 13 cytokines, C-reactive protein (CRP), glucose, and hemoglobin in AIS patients, and their relationship to stroke lateralization, type, and infarct volume. Forty-five patients with AIS were evaluated. Blood samples were taken within 72 h, and volumetric analyses performed within 1–7 days after AIS onset. Cytokines were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
104
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 47 publications
18
104
1
2
Order By: Relevance
“…Clinical and experimental studies suggest that inflammatory mechanisms play an important role in the pathogenesis of IS (18,21). More studies are performed to explain the inflammatory process in AIS and to make better treatment decisions and individualization of therapy nowadays (1,3,22,23). The biochemical parameters used routinely also were used in these studies (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical and experimental studies suggest that inflammatory mechanisms play an important role in the pathogenesis of IS (18,21). More studies are performed to explain the inflammatory process in AIS and to make better treatment decisions and individualization of therapy nowadays (1,3,22,23). The biochemical parameters used routinely also were used in these studies (21).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CRP was strongly associated with the prognostic outcome after AIS (1,19,24,25). Ormstad et al (1) found that CRP played an important role in the progression of cerebral tissue injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokines have been broadly classiied based on their receptor homology, their overall action as pro-versus anti-inlammatory, or their membership into the tumor necrosis factor, lymphokine, interleukin (IL-) and interferon (IFN-) families [9]. Cytokine receptor classes include the tumor necrosis factor receptor family, interleukin-1 receptor family, Class-II cytokine receptor family which includes interferon receptors and the IL-10 receptor, and Class-I or hematopoietin cytokine receptors which includes receptors of the IL-2, IL-3, and IL-6 family, as well as homodimeric receptors [9,[27][28][29][30].Similar to their efects in the periphery, CNS cytokines are known to regulate the production of other cytokines. They can also alter the BBB, recruit inlammatory cells and inluence neurotransmiter metabolism (monoamines, serotonin, dopamine and glutamate) [31][32][33].…”
mentioning
confidence: 99%